Réponses

Meilleure réponse !
2014-03-16T18:15:05+01:00
Rac(5)*rac(3) = rac(5*3) = racine(15)

rac(2)*rac(7) = racine(14)

2 rac(3) = rac(4)*rac(3) = rac(12)

3 rac(2) = rac(9)*rac(2) = rac(18)

rac(5)*rac(15) = rac(5*15) = rac(75) = rac(25*3) = rac(25)*rac(3) = 5 rac(3)

rac(7)*rac(21) = rac(7)*rac(3*7) = rac(7)*rac(3)*rac(7) = 7 rac(3)

rac(4/9) = rac(4)/rac(9) = 2/3

rac(1/16) = rac(1)/rac(16) = 1/4

rac(49/25) = rac(49)/rac(25) = 7/5

2/7 rac(49/64) = 2/7 * rac(49)/rac(64) = 2/7 * 7/8 = 14/56 = 7/28 = 1/4